The most potential principles of social media. (April 2016) - Hsieh, Ming-Yuan
Abstract: In this hyper-competitive and dynamic contemporary social media era, the need to satisfy a broad range of diversified users can present a challenge to technology companies. In order to identify the most potential principles of social media, this research paper cross-applies the Quality Function Deployment of House of Quality (QFD-HOD) method and the Multiple Criteria Decision Making (MCDM) method to synthetically cross-evaluate the results of completed questionnaires given to experts across various fields. This evaluation is done through interplay analyses of sixteen social media user desires (WHATs) and sixteen social media technological functions (HOWs). To further strengthen the research reliability and validity, the Analytical Network Process (ANP) model is applied to re-testify these measured consequences from an individual, group and environmental perspectives employing the Social Cognitive Theory (SCT). The results conclude that the five most significant social media principles are multiple device accessibility, content reality, individualizational, keyword-search engine and identity feature functions that will largely fulfill the needs of social media users.